Cloud based IoT Electronic Healthcare Data Warehouse Integration in emerging 5G Health Grid Ecosystem - Onyebuchi, Amaonwu; Matthew, Ugochukwu Okwudili; Kazaure, Jazuli Sanusi; Nwanagwaugwu, Andrew Chinonso; Nwamouh, Ubochi Chibueze; Adamu, Umar Abdu (Journal of ISMAC, 2023)
The integration of heterogeneous enterprise cloud data warehouses enables the formation of national health grid ecosystem that links public and private health databases to enable supervision of healthcare utilities, costs, quality of care and observance of national healthcare administrative protocols. The development of cloud data warehouse requires information communication technology to condense the costs of patient’s healthcare by supporting care, away from hospitals, where increasingly detailed data can move from patients to centralized cloud server data warehouse, allowing efficiency in diagnosis and treatment options. The global democratization of 5G telecommunication broadband creates entirely new use case scenarios for consumers addressing healthcare sector and industries, intending to improve citizen’s life expectancy. The improved data rate transmission revolutionizes healthcare sector and offers prospects that enable the telecommunication merchants to penetrate the supply chains and initiate partnerships that profit the entire healthcare business ecosystem. This paper analyses the 5G network implementation business potentials, focusing on the 5G business opportunities that originate from industrial healthcare automation, allowing patient data aggregation required for citizens’ healthcare management. The research entrenches the 5G radio frequency access network and distributed cloud IoT server systems in constructing a healthcare grid data warehouse to enable self-optimized service-level agreements. Moreover, this paper observes that the healthcare sector prioritized telecommunication operators when partnership issues were debated above every other service sector addressing healthcare development. The cloud IoT platform offers solution to synchronize-able global device connectivity management for e-healthcare and demonstrates how these improvements enable development of new systems for public healthcare policy formulation and delivery in Nigeria.